Test-as-a-Service: Application to Security Testing - Pereira, Nuno José Matos (2016)
In a world where software gradually plays a key role daily, a failure may bring unpleasant consequences for its users. An example of a serious failure was the case Apple iCloud security exploit in 2014 where several private photos of celebrities have been accessed without permission[icl14a][icl14b]. Apart from economic and commercial implications, these faults lead to loss of trust in software by users, thus leading to the consequent search for an alternative and even result in leaving the old software for a new alternative. To address these shortcomings, the software industry started to use software testing to make sure that the software contains the minimum possible failures before is deployment. Software tests are used to analyse the program, namely to search some bugs. This analysis can be done without program execution (static analysis) or during execution (dynamic analysis). Static analysis tools can be used to check for potential execution of the program that have not been prematurely aborted due to unexpected event at runtime, not ensuring that the program will display the correct result. We studied some static analysis tools, JSFlow, JSPrime and TAJS, which analyse JavaScript code. These tools have been modified so they can be integrated into the Nibiru framework. Nibiru is a modular framework that aims to help in the implementation of software testing. It uses a micro-services architecture, enabling the use of multiple programming languages in his modules and has the ability to enable the implementation of its modules on multiple machines. So far the Nibiru has three operating modules and its ready to start growing with the community, so they can contribute in the construction of new modules or make small adjustments on the existing testing software to integrate the Nibiru framework.